Peningkatan Produktivitas Pada UMKM Batik Sendang Lestari Di Kelurahan Bendogerit Dengan Memafaatkan Limbah Kertas - Halid Adli; Wahyu Fahrul Ridho (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2023)
In general, copper is the main ingredient for making batik stamps in Indonesia, where the price is quite expensive, so it is considered not affordable for all groups, resulting in the use of reverse stamps only in certain circles. Over time, another alternative emerged, namely paper-based batik stamps. Paper is a material that is easy to find and inexpensive. Based on this, making batik stamps from paper has advantages and disadvantages as well as the characteristics of batik stamps used from various types of paper will be explained in this study. The method used is a qualitative-descriptive trial. The process of collecting data is done through experiments and documentation. The results of the research show that making batik stamps from paper is quite simple, does not require a special process and can be done by yourself. The advantage is that it is made faster and the materials are cheap. The downside is that this paper is not durable because the more it is used, the quality of the batik stamp will decrease because the paper cannot retain heat properly. It is hoped that the implementation of these innovations will encourage MSMEs players to be aware of the benefits and improve resource efficiency, such as cost savings, competitive advantage, and access to new markets.